"I don't eat when I'm sick": Older people's food and mealtime experiences in hospital. (March 2017) - Hope, Kelti; Ferguson, Maree; Reidlinger, Dianne P.; Agarwal, Ekta
Highlights: There is little in the literature on the food and mealtime experiences of older hospital patients, even though it is commonly known that their dietary intake is sub-optimal during hospitalisation. Sub-optimal food intake during hospitalisation is associated with adverse health-related outcomes. Barriers to adequate food intake are multifactorial and complex, and require multilevel interventions, including a change in the awareness and attitude towards food amongst healthcare staff and older hospital patients. Abstract: Background: Inadequate dietary intake is a common problem amongst older acute-care patients and has been identified as an independent risk factor for in-hospital mortality. This study aimed to explore whether food and mealtime experiences contribute to inadequate dietary intake in older people during hospitalisation. Methods: This was a qualitative phenomenological study, data for which were collected using semi-structured interviews over a three-week period. During this time, 26 patients aged 65 years or more, admitted to medical and surgical wards in a tertiary acute-care hospital, were asked to participate if they were observed to eat less than half of the meal offered at lunch. Participants provided their perspectives on food and mealtimes in hospital. Responses were recorded as hand-written notes, which were agreed with the interviewee, and analysed thematically using the framework method. Results: Twenty-five older people were interviewed across six wards. Two main themes, 'validating circumstances' and 'hospital systems', were identified. Each theme had several sub-themes. The sub-themes within validating circumstances included 'expectations in hospital', 'prioritising medical treatment', 'being inactive', and 'feeling down'. Those within 'hospital systems' were 'accommodating inconvenience', 'inflexible systems', and 'motivating encouragement'. Conclusion: Inadequate dietary intake by older hospital patients is complex and influenced by a range of barriers. Multilevel and multidisciplinary interventions based on a shared understanding of food and nutrition as an important component of hospital care are essential to improve dietary intake and reduce the risk of adverse clinical outcomes. Improving awareness of the importance of food for recovery amongst hospitalised older people and healthcare staff is a priority.